Optical Properties of \(CuInS_2\) Thin Films Prepared by Spray Pyrolysis - Thai, Tran Thanh; Hung, Pham Phi; Son, Vo Thach; Bich, Vu Thi (Communications in Physics, 2012)
Polycrystalline CuInS\(_2\) (CIS) absorber films for solar cells were prepared by spray pyrolysis of aqueuos solution of copper chloride, indium chloride and thiourea onto heated glass substrates. By optimizing the spray parameters, such as reducing/increasing the temperature of the substrate and molar ratio of Cu/In in the spraying solution, the optical characteristics of films, which are well matched to the solar spectrum, were identified. In all cases, those CIS thin films were of p-type conductivity. Transmission measurements were performed to examine the optical properties of the films; the absorption coefficient and the optical band gap of the films were calculated by transmission spectra. The absorption spectra of the films showed that this compound is a direct band gap one and its gap varied between 1.30 - 1.78 eV. Those thin films were analyzed by X-ray diffraction in order to understand the effect of layers structure on their optical properties